Nanovaccines against Viral Infectious Diseases - Heng, Wen Tzuen *; Yew, Jia Sheng *; Poh, Chit Laa * (MDPI, 2022)
Infectious diseases have always been regarded as one of the greatest global threats for the last century. The current ongoing COVID-19 pandemic caused by SARS-CoV-2 is living proof that the world is still threatened by emerging infectious diseases. Morbidity and mortality rates of diseases caused by Coronavirus have inflicted devastating social and economic outcomes. Undoubtedly, vaccination is the most effective method of eradicating infections and infectious diseases that have been eradicated by vaccinations, including Smallpox and Polio. To date, next-generation vaccine candidates with novel platforms are being approved for emergency use, such as the mRNA and viral vectored vaccines against SARS-CoV-2. Nanoparticle based vaccines are the perfect candidates as they demonstrated targeted antigen delivery, improved antigen presentation, and sustained antigen release while providing self-adjuvanting functions to stimulate potent immune responses. In this review, we discussed most of the recent nanovaccines that have found success in immunization and challenge studies in animal models in comparison with their naked vaccine counterparts. Nanovaccines that are currently in clinical trials are also reviewed.